2017
DOI: 10.1186/s12887-017-0786-z
|View full text |Cite
|
Sign up to set email alerts
|

Offering general pediatric care during the hard times of the 2014 Ebola outbreak: looking back at how many came and how well they fared at a Médecins Sans Frontières referral hospital in rural Sierra Leone

Abstract: BackgroundIn Bo district, rural Sierra Leone, we assessed the burden of the 2014 Ebola outbreak on under-five consultations at a primary health center and the quality of care for under-15 children at a Médecins Sans Frontières (MSF) referral hospital.MethodsRetrospective cohort study, comparing a period before (May-October 2013) and during the same period of the Ebola outbreak (2014). Health worker infections occurred at the outbreak peak (October 2014), resulting in hospital closure due to fear of occupationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In India, a cross-sectional survey among PHC facilities during COVID-19 reported that PHC facilities are constrained due to their weak infrastructure (eg, limited physical space, inadequate ventilation, suboptimal infection prevention, and control measures) 33 (#747, Type V). Similarly, provision of pediatric primary care could not be sustained throughout the EVD outbreak in Sierra Leone due to hospital closure and HCW infections 71 (#425, Type II). Effective primary care mental health services in low-resource settings can be challenging, as demonstrated in Liberia post-EVD 72 (#95, Type IV).…”
Section: Resultsmentioning
confidence: 99%
“…In India, a cross-sectional survey among PHC facilities during COVID-19 reported that PHC facilities are constrained due to their weak infrastructure (eg, limited physical space, inadequate ventilation, suboptimal infection prevention, and control measures) 33 (#747, Type V). Similarly, provision of pediatric primary care could not be sustained throughout the EVD outbreak in Sierra Leone due to hospital closure and HCW infections 71 (#425, Type II). Effective primary care mental health services in low-resource settings can be challenging, as demonstrated in Liberia post-EVD 72 (#95, Type IV).…”
Section: Resultsmentioning
confidence: 99%
“…11, 35) Disability, Basic Health and Welfare Right to the best possible health and to healthcare (Art. 24) Disrupted health service access; [ 27 , 30–38 , 57 ] except for some rural districts less affected by Ebola, utilization of primary care remained robust despite the outbreak; [ 39 ] Unavailability of medication; [ 30 , 65 ] Worsening of children and maternal health care quality; [ 26 , 31 , 33 , 35–37 , 40–43 , 55 , 65 ] Lack of child-centered health services; [ 25 , 27 , 30 , 40 ] High EVD mortality rate, especially in very young children (<12 months of age); [ 25 , 30 ] Exacerbation in overall infant, child and maternal mortality (specifically in teenage girls); [ 25 , 26 , 30 , 35 , 42 , 43 , 55 , 57 , 64 ] Worsening of common diseases’ management; [ 27 , 28 , 34 , 40 , 44 , 45 , 55 , 64 , 65 , 75 ] Increased risk of malnutrition and undernutrition; [ 55 , 57 , …”
Section: Data Extractionmentioning
confidence: 99%
“…A decline of 46% - 83.8% in pediatric ED admission was demonstrated at the pediatric ED during the COVID-19 pandemic [ 51 , 55 , 56 , 58 60 ]. A 36% decline in under-5 children consultation was reported during the Ebola outbreak at the primary healthcare level [ 61 ].…”
Section: Resultsmentioning
confidence: 99%